Factors Influencing the Incidence of Iron Deficiency Anemia in Pregnant Women: A Systematic Review: Article - Sugesti, Retno (Journal of health research and technology, 2025)
Background: Maternal anemia has significant negative impacts on both mothers and babies. The risk of death in pregnant women with severe anemia is reported to be twice as high as in those without severe anemia. This article aims to identify the factors contributing to iron deficiency anemia in pregnant women. Materials and Methods: In this study, literature was searched through various online databases, including PubMed, BMC Public Health, and Google Scholar. This systematic review included only freely accessible articles published between 2020 and 2024. The research questions were formulated using the PET framework model and using PRISMA. Result: The literature search yielded a total of 174,146 articles, of which 156,763 were removed due to duplication, and 63 were excluded as they were published before 2020. After the initial screening, 16,294 articles remained but were further filtered out due to irrelevant abstracts and failure to meet inclusion criteria. A second screening of full-text articles left 1,018, which were further narrowed down based on inclusion criteria, resulting in 15 articles. Comclusion : This study concludes that anemia in pregnant women is caused by internal factors, such as biological and physiological conditions, as well as external factors, such as socioeconomic status and access to healthcare. These factors interact with each other, highlighting the need for a comprehensive approach to prevention and management.